Pengaruh Inovasi Pembelajaran Berbasis Proyek dalam Meningkatkan Kualitas Belajar Pada Siswa SMPIT Rabbi Radhiyya Curup - Herawati, Herawati; Aderempas, Tere; Murniyanto, Murniyanto; Istan, Muhammad (LPPM Institut Pendidikan Nusantara Global, 2024)
This study aims to examine the influence of project-based learning innovations on improving the quality of learning among students at SMPIT Rabbi Radhiyya Curup. The study employs a descriptive qualitative research design. This design was chosen because the research objective is to gain a deep understanding of the impact of project-based learning innovation on student quality, as well as how this innovation's implementation is perceived and interpreted by students, teachers, and other relevant parties. The results of the study indicate that the implementation of project-based learning at SMPIT Rabbi Radhiyya Curup has proven to have significant goals and benefits in supporting the designated education program. Through this method, participants can develop a better understanding, critical skills, teamwork, and relevance to the real world.